Emission mitigation scenarios for the rural sector of the State of Chiapas using state models and transitions - Covaleda, Sara; Paz-Pellat, Fernando; Ranero, Alejandro (Instituto de Ecología, A.C., 2018)
In the State of Chiapas, where emissions from the LULUCF (Land Use, Land Use Change and Forestry) and Agricultural (including livestock) sectors cover 78% of total emissions, it is necessary to propose mitigation activities in the rural sector (in particular the reduction of emissions from deforestation and forest degradation). In this work, abatement cost curves and mitigation scenarios for Chiapas were generated using state and transition models prepared for eight regions of the state. These models allow us to know the impacts associated with the transition between an initial state (land use or vegetation type) and a final one in terms of carbon and socio-economic factors. The restrictions considered were: positive and negative opportunity costs, subsidy, credit and interest rate. The state has great potential to mitigate emissions in the rural sector, particularly the Selva Maya and Altos regions. The analysis of different scenarios shows that an opportunity cost for USD 4/t CO2 – USD 6/t CO2 is enough for a good portion of the GHG mitigation potential of Chiapas. The subsidy and credit for the implementation activities affects the mitigation potential for certain ranges of opportunity costs, also, the activities with negative opportunity costs are an opportunity area to mitigate emissions reorienting public policies. To improve the analysis capacity of the models it is necessary to encourage research on activities related to forest degradation, sustainable forest management and increase of forest and agricultural carbon stores.